1997
DOI: 10.1007/s004120050271
|View full text |Cite
|
Sign up to set email alerts
|

ASE-1: a novel protein of the fibrillar centres of the nucleolus and nucleolus organizer region of mitotic chromosomes

Abstract: A novel nucleolar component has been identified and cloned using a human autoimmune serum. This antigen, as inferred from the cDNA sequence, is an Mr 55000 protein. Immuno blot analysis, however, of both the native protein and the in vitro translation products of the cDNA showed that they migrate on SDS-PAGE at an apparent molecular mass of 90000 A BLAST search using the cDNA sequence indicated that it is in an antisense orientation to and overlaps the gene of the DNA repair enzyme ERCC-1. An open reading fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…1). ASE-1 was identified as a human autoimmune antigen that locates to fibrillar centers in interphase and to nucleolar organizer regions during cell division (48). It was also reported that ASE-1 colocalizes with UBF throughout the cell cycle and that the two proteins bind each other.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1). ASE-1 was identified as a human autoimmune antigen that locates to fibrillar centers in interphase and to nucleolar organizer regions during cell division (48). It was also reported that ASE-1 colocalizes with UBF throughout the cell cycle and that the two proteins bind each other.…”
Section: Resultsmentioning
confidence: 97%
“…Initially, ASE-1 was predicted as an open reading frame present in the antisense orientation to the gene coding for the DNA repair enzyme ERCC-1 and was thus given the name ASE-1, standing for antisense to ERCC-1 (46). Subsequently, another group identified the gene product as a nucleolar protein by screening a HeLa cDNA library with a human autoimmune serum (48). They showed that ASE-1 occurred at the fibrillar center in interphase and then in the nucleolar organizer regions during cell division.…”
Section: Discussionmentioning
confidence: 99%
“…1 Lung Cancer Center, Kyungpook National University Medical Center; Departments of 2 Biochemistry and Cell Biology, may be a member of the RNA polymerase I transcription complex that synthesize rRNA precursors, thus implicating CD3EAP in cell proliferation (11). It has been reported that haplotypes of 3 single-nucleotide polymorphisms (SNP), rs1970764T>C (PPP1R13L IVS8-1435), rs967591G>A (-8358 from PPP1R13L, or -21 from CD3EAP), and rs11615G>A (ERCC1 N118N), are associated with the risk of basal cell carcinoma, breast cancer, and lung cancer (12)(13)(14) suggesting that genetic variation(s) in the 19q13.3 region may affect the susceptibility to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This 72-kDa protein was initially discovered as a human autoantigen (encoded antisense in the region of the ERCC1 gene, or ASE-1) and was shown to interact with UBF in vitro and to colocalize with UBF in nucleoli, suggesting that it might have a role in Pol I transcription, although its function was unknown (37). Later, the same protein was rediscovered as one associated with the CD3ε-signaling module of the T-cell receptor, named CAST (CD3ε-associated signal transducer), and was shown to be important in signaling and gene expression following T-cell activation (40).…”
mentioning
confidence: 99%